SURGICAL TREATMENT OF BREAST CANCER: FROM THE CONCEPT OF ERADICATION TO AESTHETIC SURGERY - I. K. Vorotnikov; V. P. Letyagin; I. V. Vysotskaya; V. Yu. Sel’chuk; D. A. Burov; A. V. Pavlov (Опухоли женской репродуктивной системы, 2018)
This article discusses the historical development of oncoplastic surgery, describes the main stages of oncoplastic breast surgery, indications and contraindications for it, and the algorithms for choosing an appropriate surgical technique for patients with breast cancer.